Sayaw a documentary on Philippine ethnic dances and rites - Cultural Center of the Philippines; Obusan, Ramon A.; Villaruz, Basilio Esteban S. (Manila The Center, 1992)
Features the variety of pre-Spanish dance and dance traditions of the peoples of the Philippines.
VHS.
Narration, Tony O. Mabesa ; producers, Rowena E. Concepcion, Mary Ann Ines-Loveria.
Keywords: Dancing -- History. -- Philippines; Documentary